2016
DOI: 10.1038/mp.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of cognitive functions and educational attainment in UK Biobank (N=112 151)

Abstract: People's differences in cognitive functions are partly heritable and are associated with important life outcomes. Previous genome-wide association (GWA) studies of cognitive functions have found evidence for polygenic effects yet, to date, there are few replicated genetic associations. Here we use data from the UK Biobank sample to investigate the genetic contributions to variation in tests of three cognitive functions and in educational attainment. GWA analyses were performed for verbal–numerical reasoning (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
371
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(401 citation statements)
references
References 74 publications
21
371
1
4
Order By: Relevance
“…Hence, it seems that the effect is caused by a certain capacity to acquire education that is not always realized. We postulate that, in addition to being correlated with cognitive ability (32,33), POLY EDU is capturing a portion of the propensity to long-term planning and delayed gratification. To address the question of whether and how these results could be extended to other populations and other time periods it should first be emphasized that the negative selection observed here is likely an example of gene-environment interaction, that is, both the direction of the effect and its magnitude could and would change given a different socioeconomic environment (5,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems that the effect is caused by a certain capacity to acquire education that is not always realized. We postulate that, in addition to being correlated with cognitive ability (32,33), POLY EDU is capturing a portion of the propensity to long-term planning and delayed gratification. To address the question of whether and how these results could be extended to other populations and other time periods it should first be emphasized that the negative selection observed here is likely an example of gene-environment interaction, that is, both the direction of the effect and its magnitude could and would change given a different socioeconomic environment (5,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Bivariate GCTA-GREML 48 and linkage disequilibrium (LD) score regression 50 were used to derive genetic correlations between TMT measures and VNR in UK Biobank. 32 LD score regression was also used to estimate genetic correlations between trail making measures in UK Biobank and trail making part A, trail making part B, general cognitive function, processing speed and memory from the CHARGE consortium (participants aged 45 years or older) meta-analyses of these cognitive phenotypes. 31,33,51 Gene-based association analysis MAGMA 52 was used to derive gene-based associations using the summary results of the three GWAS for trail making.…”
Section: Snp-based Heritability and Genetic Correlationsmentioning
confidence: 99%
“…[28][29][30] A recent genome-wide association study (GWAS) of trail making part A and part B in a sample of around 6000 individuals did not find any genome-wide significant hits; 31 however, GWAS of other cognitive phenotypes have demonstrated that much larger sample sizes are required to reliably identify significant genetic loci. 32,33 Trail making is thought to have genetic influences that are shared with other cognitive abilities, with a twin-based genetic correlation of 0.48 reported between trail making, measured as the ratio between trail making part A and trail making part B, and general cognitive function, and 0.52 with working memory. 34 In addition to a relatively poor understanding of the molecular genetic underpinnings of TMT, its cognitive and psychometric architecture merits further research.…”
Section: Introductionmentioning
confidence: 99%
“…A second POLY COG score was constructed using data from another GWAS study of educational attainment and related phenotypes (Davies et al, 2016). In this study, 1,115 SNPs reached GWAS significance, of which 15 were independent (linkage pruned) signals.…”
Section: Variant Calling and Computing Poly Cogmentioning
confidence: 99%